Causes of Death According to Death Certificates in Individuals with Dementia: A Cohort from the Swedish Dementia Registry - Garcia-Ptacek, Sara; Kåreholt, Ingemar; Cermakova, Pavla; Rizzuto, Debora; Religa, Dorota; Eriksdotter, Maria (Journal of the American Geriatrics Society, 2016)
OBJECTIVES: The causes of death in dementia are not established, particularly in rarer dementias. The aim of this study is to calculate risk of death from specific causes for a broader spectrum of dementia diagnoses. DESIGN: Cohort study. SETTING: Swedish Dementia Registry (SveDem), 2007-2012. PARTICIPANTS: Individuals with incident dementia registered in SveDem (N = 28,609); median follow-up 741 days. Observed deaths were 5,368 (19%). MEASUREMENTS: Information on number of deaths and causes of mortality was obtained from death certificates. Odds ratios for the presence of dementia on death certificates were calculated. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using Cox hazards regression for cause-specific mortality, using Alzheimer's dementia (AD) as reference. Hazard ratios for death for each specific cause of death were compared with hazard ratios of death from all causes (P-values from t-tests). RESULTS: The most frequent underlying cause of death in this cohort was cardiovascular (37%), followed by dementia (30%). Dementia and cardiovascular causes appeared as main or contributory causes on 63% of certificates, followed by respiratory (26%). Dementia was mentioned less in vascular dementia (VaD; 57%). Compared to AD, cardiovascular mortality was higher in individuals with VaD than in those with AD (HR = 1.82, 95% CI = 1.64-2.02). Respiratory death was higher in individuals with Lewy body dementia (LBD, including Parkinson's disease dementia and dementia with Lewy bodies, HR = 2.16, 95% CI = 1.71-2.71), and the risk of respiratory death was higher than expected from the risk for all-cause mortality. Participants with frontotemporal dementia were more likely to die from external causes of death than those with AD (HR = 2.86, 95% CI = 1.53-5.32). CONCLUSION: Dementia is underreported on death certificates as main and contributory causes. Individuals with LBD had a higher risk of respiratory death than those with AD.
Keywords: Registries; survival analyses; Švédsko; kardiovaskulární nemoci; dementia; Humans; demence s Lewyho tělísky; registrace; Sweden; kohortové studie; death certificate; respiratory death; Female; Aged; Lewy Body Disease; úmrtní listy; Lewy body dementia; vaskulární demence; senioři; lidé; Alzheimer Disease; Death Certificates; Alzheimerova nemoc; nemoci dýchací soustavy; Dementia, Vascular; Respiratory Tract Diseases; Cohort Studies; ženské pohlaví; Cardiovascular Diseases; Male; Alzheimer's; Aged, 80 and over; Cause of Death; senioři nad 80 let; příčina smrti; mužské pohlaví; causes of death